2018
DOI: 10.1111/ijlh.12785
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive re‐evaluation of historical von Willebrand disease diagnosis in association with whole blood platelet aggregation and function

Abstract: von Willebrand disease is associated with impaired VWF-dependent whole blood platelet functions that match traditional VWF measurements. We detected normal VWF in 25% of historically diagnosed patients, mainly type 1 patients, implying that there is a need to systematically re-evaluate historical VWD diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
0
15
2
Order By: Relevance
“…The WB-RIPA in patients with a BS ≥4 (an abnormal bleeding tendency 20 ) was highly variable, however, and the overall correlation between WB-RIPA and BS in individual patients was low. These results tended to contradict those of Nummi et al14 that had previously demonstrated a correlation between WB-RIPA and BS in type 1 VWD. It may be that the smaller number of patients (n = 7) relative to ours (n = 55) influenced the findings.…”
contrasting
confidence: 79%
See 3 more Smart Citations
“…The WB-RIPA in patients with a BS ≥4 (an abnormal bleeding tendency 20 ) was highly variable, however, and the overall correlation between WB-RIPA and BS in individual patients was low. These results tended to contradict those of Nummi et al14 that had previously demonstrated a correlation between WB-RIPA and BS in type 1 VWD. It may be that the smaller number of patients (n = 7) relative to ours (n = 55) influenced the findings.…”
contrasting
confidence: 79%
“…It may be that the smaller number of patients (n = 7) relative to ours (n = 55) influenced the findings. In addition, Nummi et al reported that using a ristocetin concentration at 0.8 mg/mL did not completely identify all type 1 and type 2 VWD patients, and that a ristocetin concentration at 0.6 mg/mL was more sensitive (100%) to the classification of type 1 individuals. Our WB‐RIPA assay used a ristocetin concentration at 1.2 mg/mL contained in the commercially available reagents commonly utilized for conventional RIPA with platelet‐rich plasma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To differentiate type 1 from type 2 vWD, vWF:RCoF to vWF:Ag ratio of <0.7 was used. 7 Undetectable vWF:Ag and RCoF with very low FVIII level (1-9 IU/dL) led to the diagnosis of type 3 vWD. 7 Multimer analysis, von Willebrand collagen binding activity, and ristocetin-induced platelet aggregation were not performed due to the nonavailability and cost constraints.…”
Section: Methodsmentioning
confidence: 99%